Preoperative diagnosis of tumor grade and type in endometrial cancer by pipelle sampling and hysteroscopy: Results of a French study. (December 2016) - Phelippeau, Juliette; Canlorbe, Geoffroy; Bendifallah, Sofiane; Naoura, Iptissem; Lefevre, Marine; Ballester, Marcos; Daraï, Emile
Abstract: Background: No data are available to establish whether operative hysteroscopy is superior to standard pipelle sampling to determine histological and grade status in endometrial cancer (EC). The aim of this study was to evaluate whether pipelle device sampling or operative hysteroscopy had an impact on preoperative determination of histological and grade status in EC and consequently on surgical management. Methods: Data of 224 women with EC receiving primary surgical treatment between 2002 and 2014 were abstracted from a single institution with maintained database. Women were staged on the basis of preoperative and final pathological findings according to the 2009 International FIGO classification. Discrepancies in pathological analysis were assessed between pipelle sampling or operative hysteroscopy and final histology. Values of p < 0.05 were considered to denote significant differences. Results: 149 women underwent preoperative pipelle sampling and 75 operative hysteroscopy. Global discrepancies between pre-operative and post-operative analysis was 20.8% versus 20.0% in the pipelle device and operative hysteroscopy group, respectively, with no significant difference considering type 1 grade 1 or 2 versus type 1 grade 3 versus type 2 EC. Discrepancies in histological type between preoperative and final histology were found in 25 (16.8%) and 11 (14.7%) women in the pipelle device and operative hysteroscopy groups, respectively (p = 0.85). Discrepancies in histological grade between preoperative and final histology were found in 6 (5.8%) vs. 4 (7.0%) of the women in the pipelle device and operative hysteroscopy groups, respectively (p = 1). Conclusion: This study suggests that both pipelle sampling and operative hysteroscopy are of limited value in determining definitive histological type and grade. Additional investigations should be evaluated to better characterize the risk groups. Highlights: Both biopsies techniques have limited accuracy in assessing type and grade in EC. 20% of women are underestimated or overestimated by final analysis. Discrepancies could lead to inadequate initial management. There is no difference between pipelle device and operative hysteroscopy. Additional investigation approaches should be evaluated.